AIE phenomena of a cyanostilbene derivative as a probe of molecular assembly processes. (30th November 2016) - Ito, Fuyuki; Fujimori, Jun-ichi; Oka, Narumi; Sliwa, Michel; Ruckebusch, Cyril; Ito, Syoji; Miyasaka, Hiroshi
Abstract : The initial processes of the crystallization of a solute molecule, 1-cyano- trans -1, 2-bis-(4′-methylbiphenyl)-ethylene (CN-MBE) in binary solution (water and acetone), were investigated by means of fluorescence spectroscopy as well as scanning electron microscopy (SEM). With an increase in the volume fraction ( V w ) of the poor solvent (water) in the solution, a drastic change in the fluorescence spectra and intensity of CN-MBE was observed. This change was attributed to aggregation induced emission (AIE). By analyzing the evolution of AIE by multivariate curve resolution-alternating least squares (MCR-ALS), it was revealed that four main species appeared in the solution depending on the V w values. On the basis of molecular exciton theory, we assigned these four emissive states to the monomer, H-dimer, J-dimer, and H-aggregates. Interestingly, the J-dimer state was observed only in a V w range of 40% to 50%, just before the formation of the aggregate. This result suggests that the J-dimer plays an important role as the precursor for larger aggregates leading to crystal formation. By integrating the present results with previous work on the crystallization of CN-MBA through solvent evaporation, we discussed the dynamics of the crystallization from the viewpoint of the sequence of molecular species appearing in the aggregation in solution.